2019
DOI: 10.1109/access.2019.2915937
|View full text |Cite
|
Sign up to set email alerts
|

MPSC: A Multiple-Perspective Semantics-Crossover Model for Matching Sentences

Abstract: Sentence matching is crucial to many natural language processing (NLP) tasks. Generally, the degree of matching is measured from either of the two perspectives: topic-based match or semantic-based match. The former is to investigate if two sentences discuss the same topic, and the latter performs a deep level semantic matching of texts, which is currently the highlight in research. Deep semantic matching requires adequate modeling from the internal structure of the language objects as well as their interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Hu et al [24] proposed a context-aware crossattention mechanism that focuses on contextual information during interaction to achieve better semantic alignment. In contrast, Wang et al [28] did not perform semantic alignment of words or phrases but used full-matching, maxpoolingmatching, attentive-matching, and max-attentive-matching to achieve interaction between texts, and several studies have demonstrated the exceptional performance of this multiperspective matching mechanism [39]. Pre-training based approaches using transformer structure for supervised or unsupervised training on large scale data, represented by BERT and RoBERTa, have achieved very excellent results in the field of text matching.…”
Section: A Text Matchingmentioning
confidence: 99%
“…Hu et al [24] proposed a context-aware crossattention mechanism that focuses on contextual information during interaction to achieve better semantic alignment. In contrast, Wang et al [28] did not perform semantic alignment of words or phrases but used full-matching, maxpoolingmatching, attentive-matching, and max-attentive-matching to achieve interaction between texts, and several studies have demonstrated the exceptional performance of this multiperspective matching mechanism [39]. Pre-training based approaches using transformer structure for supervised or unsupervised training on large scale data, represented by BERT and RoBERTa, have achieved very excellent results in the field of text matching.…”
Section: A Text Matchingmentioning
confidence: 99%
“…Park et al [18] have presented a visual analytical system where a bipolar concept has been introduced in modeling. Peng et al [19] have presented a deep semantic approach over multiple perspectives in order to extract the correlation between two sentences. Prakash and Murthy [20] have presented a language specific approach for improving the performance of text-to-speech application.…”
Section: A Backgroundmentioning
confidence: 99%